Factors influencing smoking cessation counselors' intention to stay: An application of a conceptual model of intention to stay verified with path analysis - Liu, Yi-Chun; Chiang, Shih-Hung; Lai, Chung-Yu; Yen, Li-Chen; Liaw, Fang-Yih; Lin, Ming-Han; Lin, Fu-Gong; Lai, Ching-Huang; Kao, Senyeong; Chang, Yu-Tien; Wu, Chia-Chao; Chiu, Yu-Lung (Frontiers in Public Health, 2022)
Background: The Taiwanese military trains smoking cessation counselors to counsel officers and soldiers on quitting smoking as part-time. The intention to stay among smoking cessation counselors affects the promotion of smoking cessation. This study investigated smoking cessation counselors’ intention to stay by applying a conceptual model of intent to stay (CMIS) to analyze influencing factors. Methods: In this cross-sectional study, we applied the CMIS to design a questionnaire. We invited 577 smoking cessation counselors trained in the military from 2016 to 2017. The response rate was 46.7%, and the questionnaire responses of 260 military smoking cessation counselors were analyzed. We used path analysis to verify the relationships among the various aspects of the CMIS. Results: We determined that smoking cessation counselors’ intention to stay is directly affected by job satisfaction (β = 0.150, p = 0.014), job stress (β = −0.225, p < 0.001), and institutional identification (β = 0.431, p < 0.001). Career opportunities indirectly affect intention to stay through institutional identification, working environment indirectly affect intention to stay through job stress, and co-worker support and self-fulfillment indirectly affects intention to stay through job satisfaction and institutional identification. Our model could explain 36.7% of the variance in intent to stay among smoking cessation counselors. Conclusions: Our results suggest that relevant policies should be formulated to enhance smoking cessation counselors’ recognition, affirmation, and sense of belonging as related to smoking cessation counseling work, thereby raising their institutional identification and promoting their intention to stay.